The Attitudinal and Behavioral Effects of Nonfinancial Measures - Putri Paramita Agritansia; Mahfud Sholihin (Gadjah Mada International Journal of Business, 2011)
A recent study by Lau and Moser (2008) found that the use of nonfinancial measures for managerial performance evaluation is positively associated with managerial performance via procedural fairness and organizational commitment. It is not clear, however, whether the findings are generalizable to other contexts. Using very different samples, the objectives of this study are to reexamine and to extend Lau and Moser’s model. Our paper is only able to partially support their model, suggesting that management control systems should be designed to fit the contexts.